Imagining rhetoric : composing women of the early United States - Eldred, Janet Carey (Pittsburgh series in composition, literacy, and culture., 2002)
"Using a variety of sources, including novels, textbooks, letters, diaries, and memories, Janet Carey Eldred and Peter Mortensen examine the provenance, authority, and evolution of what they term "liberatory" civic rhetoric - from the early days of the republic through the antebellum years - especially as it shaped women's rhetoric and education. Imagining Rhetoric recovers what women in the early U.S. imagined instruction and practice in composition should be, and shows how this imagination shaped the possibilities and limitations of female civic rhetoric."--Jacket